Desigualdades regionais, disparidades de renda e condições sociais: uma análise dos estados da região Sudeste - Barreto, Maria Claudia Gonçalves (2010)
The historical conditions and economic decentralization process led to a strong regional disparity in levels of per capita income and living conditions among Brazilian regions, especially between Southeast, Northeast and South Brazil. The aim of this study is to analyze the regional decentralization of productive activities and their relation to income disparities and social conditions in Brazil. To do so is considered in the first part of this work the question of regional inequalities in Brazil through the issue of inheritance concentrated and the polarization of the Metropolitan Region of São Paulo (MASP) and the reversal of the polarization. Will later be analyzed the process of regional decentralization in Brazil as well as the factors and impacts of regional devolution, through the production structure and foreign trade in the regions. In the third part will be analyzed through inter-regional concentration of GDP growth between states and regions provided by the site of the Brazilian Institute of Geography and Statistics (IBGE) and IPEADATA, aiming to make subsequently, an analysis of the dynamics of concentration inter - among the regional states in the Southeast Region with social indicators. Finally it will be shown, the second selected states, the evolution of some social indicators provided by the Atlas of Human Development (1991 - 2000) and the IPEADATA (2001 2006). Will be made in the final associations between economic growth and social disparities, and to evaluate how different growth rates affect the selected states.